PENEGAKAN HUKUM LINGKUNGAN DALAM KASUS PENCEMARAN LIMBAH SERTA UPAYA HUKUM YANG DILAKUKAN MASYARAKAT DI PABRIK KAHATEX RANCAEKEK SUMEDANG, JAWA BARAT - Emma Maripah (VERITAS, 2017)
Types of violations committed by PT Kahatek in managing Waste factories derivedfrom breaches make buildings on water sources, diverting the flow of river watercikijing processing IPAL PT. Kahatex is not yet optimal so that the waste that isdischarged into the cikijing river still does not meet the Environmental QualityStandard. The role of the court has functioned but has not been maximized because inenforcing sanctions and law enforcement has not been upheld first in the absence ofIMB and AMDAL from pembangunana and processing of kahatek waste is not giventhe proper sanction, then for the government still experiencing lack of information andcooperation between local government bandung, sumedang and provinces so there isblame policy.